Attractiveness and gender dynamics in surgical specialties: a comparative analysis of French medical graduates (2017–2022) - Saadé Saadé; Arnaud Delafontaine; Johann Cattan; Doris Celanie; Gabriel Saiydoun (BMC Medical Education, 2024)
Abstract Background French medical graduates undertake a national examination at the end of their studies with a subsequent national ranking. Specialty is then chosen by each candidate according to their ranking. This study aims to describe the attractiveness of surgical specialties and the evolution of the male-female distribution among French medical graduates (FMG) from 2017 to 2022. Methods Our database included the candidates’ ranking, sex and choice of specialty from 2017 to 2022. It included all French medical graduates from 2017 to 2022 and all French medical schools. A linear regression was performed to predict future trends. Dependent variables were mean rankings and the percentage of women. The independent variable was year of application. A Pearson correlation was performed to examine any relationship with mean workweek. Results A total number of 5270 residents chose a surgical programme between 2017 and 2022. The number of residents who were assigned their desired surgical programme held stable at 878 surgical residents per year. Plastic and reconstructive surgery remained the most frequently chosen surgical programme. Thoracic and cardiovascular surgery was the least frequently chosen surgical programme between 2017 and 2022. The mean ranking for a candidate choosing a surgical programme rose significantly by 9% from 2017 to 2022 (p < 0.01). Neurosurgery exhibited the greatest fall as a surgical specialty as its rankings decreased by 163.6% (p < 0.01). Maxillo-facial surgery was the only specialty with a statistically significant increase in its rankings by 35.9% (p < 0.05). The overall proportion of women was 51.1%. Obstetrics-and-gynecology was the highest represented specialty among female candidates, with a mean of 83.9% of women. Orthopedic surgery was the lowest represented, being composed of a mean of 28.6% of women. The number of female surgical residents increased significantly over the six-year period, by 7.6% (p < 0.01). Conclusions More and more medical school graduates decide not to choose surgery for their residency programme. Some specialties continue to be attractive while many are losing their appeal. While there does appear to be progress towards gender equity, further investigation is necessary to assess its actual implementation.